Identification of an ATP-controlled allosteric switch that controls actin filament nucleation by Arp2/3 complex - Max Rodnick-Smith (Nature Portfolio, 2016)
Arp2/3 complex nucleates branched actin filaments, and is inactive in the absense of activators. Here the authors present a model of Arp2/3 autoinhibition, whereby the Arp3 C-terminal tail acts as a structural switch that blocks movement of Arp2 and Arp3 into an activated filament-like conformation.